Natural Durability and Preservative Treatability of Mangium, Manii and Sengon Woods by Cold Soaking and Hot-Cold Soaking Methods - Trisna Priadi; Gendis A Pratiwi (Masyarakat Peneliti Kayu Indonesia, 2014)
The understanding of the natural durability and preservative treatability of woods from community forests/lands is paramount to prevent biodeterioration of the woods in its utilization. This research was aimed to determine the natural durability of community woods (mangium, manii, and sengon) against subterranean termites (Coptotermes curvignatus) and dry wood termites (Cryptotermes cynocephalus), and to determine their preservative treatability with Diffusol CB applied through cold soaking and hot-cold soaking preservation methods. The results showed that manii and mangium woods were more resistant from subterranean termites and dry wood termites compared to that of sengon wood. The penetration and retension of Diffusol CB by Hot-cold preservation were twofold of that by cold soaking preservation. Penetration and retension of preservative in sengon wood was the highest, more than threefold of those in mangium (the lowest preservative treatability).Keywords: dry wood termite, natural durability, preservative treatability, subterranean termite